HISTORICAL MEMOIRS OF OPPONENTS OF THE SOVIET GOVERNMENT ON THE BASES OF HISTORICAL SOURCES (UZBEKISTAN MATERIALS) (Scientific journal of the Fergana State University, 2023)
The article gives a general overview of memoirs published in various years by figures who had a negative attitude towards the Soviet power. The authors of the article reveal the characteristic features of these memoirs and their significance as sources in the study of the Soviet period in the history of Uzbekistan.